Beating Corona Virus Disease (COVID-19) in Newborns, Infants and Toddlers - Siddiqui, Tasmiyah; Doultani, Payal Rani; Ashraf, Tayyaba (Journal of the Pakistan Medical Association, 2023)
Madam, Corona Virus Disease (COVID-19), a pandemic, has been a global concern and it is a highly contagious respiratory illness that has been fatal to around 6 million lives. Although everyone is prone to get infected by COVID-19, the fact that is often overlooked is that newborns, infants and toddlers are as likely to get COVID-19 as adults. Babies younger than one year old might have a higher chance to get COVID-19 than older children. (1) According to a case report by Alzamora et al. mother infected with COVID-19 can also, in sporadic cases, pass the disease to her baby. (2) Infants are also at risk of getting infected shortly after birth, reason being exposure to sick caregivers. Most newborn, infants and toddlers who fall prey to COVID-19 have mild or no symptoms engendering many new cases, but serious cases have also occurred leading to hospitalization. Hospitalization is associated more with the omicron variant than the delta variant. According to Morbidity and Mortality Weekly Report (MMWR) by the Centrs for Disease Control and Prevention (CDC), hospitalization of U.S. infants and children aged 0-4 years was five times more during omicron predominance than during delta surge. (3) To overcome such cases, CDC recommends COVID-19 vaccine and backs Pfizer’s and Moderna’s COVID-19 shots for children aged six month to five years. (4) These vaccines can prevent complications like Multisystem Inflammatory Syndrome and Long COVID, which can be debilitating for young children. Vaccination can also protect children, which in turn minimize the possibility of transmission of disease to others. Furthermore, U.S. Food and Drug Administration (FDA) has also expanded the approval of the COVID-19 treatment Velkury (Remdesivir) to include pediatric patients 28 days of age and older weighing at least 3 kilograms with positive results of direct SARS-CoV-2 viral testing. (5) With COVID-19 rearing its head again in Pakistan, vaccination of vulnerable populations like newborns, infants and toddlers must be an urgent step to stem the spread of virus because tomorrow may be too late. Besides, Remdesivir, which was previously approved for certain adults, can now be put to good use for treating infants as young as 28 days old so that progression in hospitalization and critical illness in pediatric patients of Pakistan be cut down.